Correction to: A novel impedimetric sensor for trace level detection of dimethyl sulfide (DMS) - Iden, Hassan (2020)
The original version of the article was published with errors in the Eq. 3, 4, 5, 6 and 7. These are corrected by publishing this correction article. The correct equations are given below.